2014
DOI: 10.3109/07420528.2014.901973
|View full text |Cite
|
Sign up to set email alerts
|

The influence of women’s attachment style on the chronobiology of labour pain, analgesic consumption and pharmacological effect

Abstract: Circadian variation in biological rhythms has been identified as affecting both labour pain and the pharmacological properties of analgesics. In the context of pain, there is also a growing body of evidence suggesting the importance of adult attachment. The purpose of this study was to examine whether labour pain, analgesic consumption and pharmacological effect are significantly affected by the time of day, and to analyse whether this circadian variation is influenced by women's attachment style. This prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Many patients with rheumatoid arthritis (RA) present a circadian rhythm in the severity of symptoms, with a significant worsening in the morning. Previous studies have shown that the change of pain threshold has an obvious circadian rhythm [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Many patients with rheumatoid arthritis (RA) present a circadian rhythm in the severity of symptoms, with a significant worsening in the morning. Previous studies have shown that the change of pain threshold has an obvious circadian rhythm [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Debon et al 5 observed significantly longer effect of epidural ropivacaine during the first stage of labour in the diurnal period. Costa-Martins et al 6 , using patient-controlled epidural analgesia, observed longer pharmacological effect during daytime and longer latency period at night. Chassard et al 7 found temporal pattern in the duration of intrathecal plain bupivacaine with a 25% variation during daytime, with a peak around noon.…”
Section: Discussionmentioning
confidence: 97%
“…[1][2][3][4] In order to establish if neuraxial local anaesthetics present time-dependent effects, numerous chronobiological studies were conducted in labour pain analgesia. [5][6][7][8]13 Although only two studies reported that time of day did not appear to influence the duration of analgesia during labour produced by intrathecal local anaesthetics or opioids 9,10 , the results of most studies were able to produce a consistent picture with peaks in the morning or at noon. 4,5,7,8 The pharmacological effect regarding intrathecal or epidural administration of local anaesthetics was longer in the diurnal period 4,8,13 , and the latency period was longer at night 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…many patients with RA present a circadian rhythm in symptoms severity with a significant worsening in Journal of Complementary Medicine & Alternative Healthcare the morning. Additionally, studies have shown that the change of pain threshold had obvious circadian rhythm [5][6]. It has been recognized that acupuncture, as an effective means of treatment, could relieve various kinds of pain syndromes [7][8].…”
Section: Introductionmentioning
confidence: 99%